2001
DOI: 10.1073/pnas.211106398
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection and growth of bacteria in the cytosol of mammalian host cells

Abstract: Most facultative intracellular bacteria replicate in specialized phagosomes after being taken up by mammalian cells. Relatively few intracellular bacteria escape the phagosomal compartment with the help of cytolytic (pore-forming) proteins and replicate in the host cell cytosol. Without such toxins, intracellular bacteria cannot reach this cellular compartment. To circumvent the requirement of an ''escape'' step, we developed a procedure allowing the efficient direct injection of bacteria into the cytosol of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 31 publications
10
116
2
Order By: Relevance
“…This suggests that bacterial cell disruption and subsequent plasmid release is an autocatalyzing process probably initiated by the spontaneous lysis of a single bacterial cell which releases phage lysin (in the case of pSP118) and other peptidoglycan-hydrolyzing enzymes subsequently disrupting most other carrier bacteria present in the target cell thus resulting in the release of sufficient plasmid DNA to warrant expression of the plasmid-encoded gene by the target cell. The observation that microinjection of S. typhimurium carrying the same plasmid (pSP118) yields considerably fewer EGFP-expressing cells than even the L. monocytogenes DtrpS strain with pSP0 supports this assumption; S. typhimurium is virtually unable to replicate in Caco-2 cell cytosol after microinjection 23 and hence the amount of plasmid DNA released by spontaneous lysis of these carrier bacteria will be rather low and hence EGFP expression less efficient.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This suggests that bacterial cell disruption and subsequent plasmid release is an autocatalyzing process probably initiated by the spontaneous lysis of a single bacterial cell which releases phage lysin (in the case of pSP118) and other peptidoglycan-hydrolyzing enzymes subsequently disrupting most other carrier bacteria present in the target cell thus resulting in the release of sufficient plasmid DNA to warrant expression of the plasmid-encoded gene by the target cell. The observation that microinjection of S. typhimurium carrying the same plasmid (pSP118) yields considerably fewer EGFP-expressing cells than even the L. monocytogenes DtrpS strain with pSP0 supports this assumption; S. typhimurium is virtually unable to replicate in Caco-2 cell cytosol after microinjection 23 and hence the amount of plasmid DNA released by spontaneous lysis of these carrier bacteria will be rather low and hence EGFP expression less efficient.…”
Section: Discussionmentioning
confidence: 85%
“…23 By coinjection of Texas red-labelled dextran together with the bacterial carrier strains (Figure 7, right panel) we observed that EGFP expression occurred in the microinjected cell 24 h after microinjection (indicated by the yellow fluorescence caused by the overlap of the green EGFP and the red fluorescence of Texas red). As summarized in Figure 7, about 5% of the cells microinjected with the L. monocytogenes D(trpS actA) strain harboring pSP0 and more than 13% of those harboring pSP118 expressed EGFP.…”
Section: Mechanism Of Bacterial Lysis and Plasmid Release In The Cytomentioning
confidence: 93%
See 1 more Smart Citation
“…This metabolic process depends on the synthesis of Hpt, a hexose phosphate transporter protein that enables bacterial intracellular multiplication and is necessary for proliferation in mouse organs. 145,146 The lipoate ligase LplA1 is among other bacterial proteins required for growth in host cells. This enzyme is essential to perform a critical lipoyl modification in the E2 subunit of pyruvate dehydrogenase, in the presence of limiting concentrations of available host lipoyl substrates, which suggests that abortive growth is due to loss of pyruvate dehydrogenase function.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…subtilis and non-pathogenic Escherichia coli (Bielecki et al, 1990 ;Gentschev et al, 1995 ;Goebel & Kuhn, 2000 ;Goetz et al, 2001).…”
Section: Abbreviationsmentioning
confidence: 99%